Optimalisasi Akupresur sebagai Intervensi Nonfarmakologis untuk Mengatasi Insomnia pada Ibu Menopause - Sumarni Sumarni; Kusumastuti Kusumastuti; Siti Mutoharoh; Helmys Aisyah; Putri Adelia; Siti Faridatun Fannani (Lembaga Pengembangan Kinerja Dosen, 2024)
Menopause is the natural end of the menstrual cycle which usually occurs when women enter the age of 45-55 years. In addition to changes in the menstrual cycle, one of the signs and symptoms of menopausal mental disorders is insomnia. Acupressure is one of the options for overcoming insomnia. The benefits of acupressure are to increase blood circulation, stimulate the nervous system, and relax the body. The purpose of this activity is to increase the knowledge of menopausal mothers about insomnia and how to reduce insomnia with acupressure. The method used is preparation through coordination with midwives and cadres of Selokerto Village, Sempor District, Kebumen Regency. The implementation of the activity was carried out with lectures and acupressure simulations, while the evaluation and follow-up plan for the activity was carried out by evaluating the knowledge of menopausal mothers and could be carried out independently using an acupressure pocket book distributed to menopausal mothers. The number of respondents in this activity was 15 menopausal mothers. The activity went smoothly, all mothers were enthusiastic in participating in the activity. Respondents were aged between 55-74 years. The level of knowledge of respondents before the activity was carried out, most had sufficient knowledge about menopause and acupressure for insomnia. While after the activity, most of the respondents' knowledge about menopause was good. Conclusion: Community service activities can effectively increase respondents' knowledge about acupressure to overcome insomnia.